Pengaruh Pembiayaan Sektor Ekonomi Primer, SEKTOR Ekonomi Sekunder, Dan Sektor Ekonomi Tersier Terhadap Non Performing Financing (NPF) Pada Perbankan Syariah Di Indonesia Periode 2010-2015 (Maret) - Imro Atul Mufidah; Fatin Fadhilah Hasib (Universitas Airlangga, 2016)
The purpose of this study is to find out the influence of financing primary sector, secondary sector, and tertiary sector toward Non Performing Financing (NPF) of Islamic Banking In Indonesia. Quantitative approach applied in this study as a research method. Furthermore, a technique of data analysis used is multiple linier regression to analyse the impact of independent variable toward dependent variable. The independent variable are financing primary sector, secondary sector, and tertiary sector. Meanwhile, NPF is the dependent variable. The result of the study shows that financing partially in primary sector influenced NPF significantly. Whereas, partially secondary sector and tertiary sector did not influence significantly to NPF. The result of simultance test indicated that the growth of financing primary sector, secondary sector, and tertiary sector influenced significantly to NPF of islamic banking.